Long-term Effects of the Strong African American Families Program on Youths’ Alcohol Use - Brody, Gene H. (2010)
OBJECTIVE: This report extends earlier accounts by addressing the effects of the Strong African American Families (SAAF) program across 65 months. Two hypotheses were tested: (a) Rural African American youths randomly assigned to participate in SAAF would demonstrate lower rates of alcohol use more than 5 years later than would control youths, and (b) SAAF’s effects on deterring the onset of alcohol use in early adolescence would carry forward to mediate the program’s long-term effects. METHOD: African American youths in rural Georgia (M age, pretest = 10.8 years) were assigned randomly to the SAAF group (n = 369) or a control group (n = 298). Past-month alcohol use was assessed at pretest and at 9, 18, 29, 53, and 65 months after pretest. RESULTS: SAAF participants increased their alcohol use at a slower rate than did adolescents in the control condition across the follow-up assessments. At the 65-month assessment, SAAF participants reported having drunk alcohol half as often as did youths in the control group. Consistent with the second hypothesis, SAAF’s effects on deterring initiation carried forward to account for its effects on alcohol use across time. CONCLUSIONS: Training in protective parenting processes and self-regulatory skills during preadolescence may contribute to a self-sustaining trajectory of disinterest in, and avoidance of, alcohol use during adolescence when peers begin to model and sanction it.